PERSEPSI PETANI TERHADAP PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKTIVITAS USAHATANI JAGUNG (Zea mays, L) DI DESA GELONG KECAMATAN ADONARA TIMUR, KABUPATEN FLORES TIMUR - Yohana Sabu Walen; Mustafa Abdurrachman; Maria Bano (Undana Press, 2021)
This research was conducted in Gelong Village, Adonara Timur District, East Flores Regency from August to September 2020. This study aims to determine; 1) Knowing the role of agricultural instructors in increasing the productivity of corn (Zea mays, L) farming in Gelong Village, East Adonara District, East Flores Regency, 2) Knowing farmer's perceptions of the role of agricultural instructors in increasing corn farming productivity in Gelong Village, East Adonara District, East Flores Regency. The determination of the location of this research was carried out deliberately based on the consideration that this location is one of the central areas of corn production. The population in this study were all corn farmers in Gelong Village, as many as 25 families. All of them were set as samples. To find out the first objective, the data were analyzed descriptively quantitatively, and to determine the second objective the data were analyzed descriptively using a Likert scale. The results of the data analysis showed that: 1) The role of agricultural extension agents was satisfactory in increasing the productivity of corn farming in Gelong Village. There are 5 roles played by agricultural extension agents related to efforts to increase maize productivity, namely: as a communicator, innovator, educator, facilitator, and motivator. 2) Farmers' perceptions of the role of agricultural extension agents in increasing maize farming productivity in Gelong Village, Adonara Timur District, East Flores Regency are quite satisfied with the percentage of achieving a maximum score of 58.96% which is in the range > 52 - 68. This shows the existing extension agents in the research location it has played its role well as communicator, educator, innovator, facilitator, and motivator in increasing the productivity of corn farming but this has not been done optimally.